2003
DOI: 10.1002/marc.200390057
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked Poly(amido‐amine)s as Superior Matrices for Chemical Incorporation of Highly Efficient Organic Nonlinear Optical Dyes

Abstract: We report on the synthesis and characterization of new crosslinked polymeric matrices, pertaining to the class of poly(amido‐amine)s (PAAs), functionalized with highly performing nonlinear optical (NLO) heterocycle‐based dyes as side‐chain substituents. Linear, soluble, and highly crosslinked NLO‐functionalized PAA networks can be easily prepared under mild conditions. The wide‐ranging tunability of optical and mechanical properties of these matrices makes them a superior alternative to conventional high‐Tg th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Dimethyl-pepep (d-pep, Scheme 1)and pepep-isothiocianate have been synthesized [4][5][6] . Rhodamine 6G has been purchased by Fluka Chemical Co., calf thymus DNA, beta-lactoglobulin B, and Bovine Serum Albumin (BSA) were purchased by Sigma-Aldrich Chemical Co. All reagents (ethanol, dimethyl-sulfoxide) were of the highest purity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimethyl-pepep (d-pep, Scheme 1)and pepep-isothiocianate have been synthesized [4][5][6] . Rhodamine 6G has been purchased by Fluka Chemical Co., calf thymus DNA, beta-lactoglobulin B, and Bovine Serum Albumin (BSA) were purchased by Sigma-Aldrich Chemical Co. All reagents (ethanol, dimethyl-sulfoxide) were of the highest purity.…”
Section: Methodsmentioning
confidence: 99%
“…A wide effort is therefore being undertaken in order to develop efficient two-photon absorbers with high quantum efficiency and two-photon cross-section and with low bleaching for two-photon excitation [3][4][5] . We give here a detailed characterization employing both one and two photon excitation of an efficient two-photon absorber, dimethyl-pepep.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, prim ‐amino‐alkyl substituted dyes were prepared and added as co‐monomers to reaction systems leading to highly crosslinked PAA, thus obtaining PAA networks with NLO moieties covalently attached as side substituents. The very mild preparation conditions combined with the wide‐ranging tuneability of optical and mechanical properties made these matrices a valuable alternative to conventional high‐ T g thermoplastic polymers . Moreover, it was found that a stable alignment of the second order covalently attached NLO‐phores could be obtained by a three steps procedure (swelling–poling–de‐swelling) performing the last two steps under poling conditions .…”
Section: Physico‐chemical Propertiesmentioning
confidence: 99%
“…The very mild preparation conditions combined with the wide-ranging tuneability of optical and mechanical properties made these matrices a valuable alternative to conventional high-T g thermoplastic polymers. [171][172][173] Moreover, it was found that a stable alignment of the second order covalently attached NLO-phores could be obtained by a three steps procedure (swellingpoling-de-swelling) performing the last two steps under poling conditions. 174 This procedure appears widely applicable for producing composite polymeric materials with a rather stable second harmonic generation.…”
Section: Crosslinked Paas As Matrices For High-performance Nonlinear mentioning
confidence: 99%
“…Besides biomedicine and biotechnology, PAAs have been studied for potential applications in different technical fields, including heavy metal ion adsorbing resins for water purification [9][10][11][12][13] and as heterogeneous catalysts [14], highperformance nonlinear optical dyes [15,16], coating for sensing applications [17][18][19] and flame retardant agents for cotton textiles [20,21]. In this review, the potential of PAAs in biotechnology will be discussed.…”
Section: Introductionmentioning
confidence: 99%